Antigen-specific immune reactions to ischemic stroke - Urra, Xabier; Miró, Francesc; Chamorro, Angel; Planas, Anna M. (Frontiers in Cellular Neuroscience, 2014)
Brain proteins are detected in the CSF and blood of stroke patients and their concentration is related to the extent of brain damage. Antibodies against brain antigens develop after stroke, suggesting a humoral immune response to the brain injury. Furthermore, induced immune tolerance is beneficial in animal models of cerebral ischemia. The presence of circulating T cells sensitized against brain antigens, and antigen presenting cells (APCs) carrying brain antigens in draining lymphoid tissue of stroke patients support the notion that stroke might induce antigen-specific immune responses. After stroke, brain proteins that are normally hidden from the periphery, inflammatory mediators, and danger signals can exit the brain through several efflux routes. They can reach the blood after leaking out of the damaged blood-brain barrier or following the drainage of interstitial fluid to the dural venous sinus, or reach the cervical lymph nodes through the nasal lymphatics following CSF drainage along the arachnoid sheaths of nerves across the nasal submucosa. The route and mode of access of brain antigens to lymphoid tissue could influence the type of response. Central and peripheral tolerance prevents autoimmunity, but the actual mechanisms of tolerance to brain antigens released into the periphery in the presence of inflammation, danger signals, and APCs, are not fully characterized. Stroke does not systematically trigger autoimmunity, but under certain circumstances, such as pronounced systemic inflammation or infection, autoreactive T cells could escape the tolerance controls. Further investigation is needed to elucidate whether antigen-specific immune events could underlie neurological complications impairing stroke outcome.